Boosting regulatory T cell function by CD4 stimulation enters the clinic - Becker, Christian; Bopp, Tobias; Jonuleit, Helmut (Frontiers in Immunology, 2012)
Understanding tolerance mechanisms at the cellular and molecular level holds the promise to establish novel immune intervention therapies in patients with allergy or autoimmunity and to prevent transplant rejection. Administration of monoclonal antibodies (mAb) against the CD4 molecule has been found to be exceptionally well suited for intentional tolerance induction in rodent and nonhuman primate models as well as in humanized mouse models. Recent evidence demonstrated that regulatory T cells (Treg) are directly activated by non-depleting CD4 ligands and suggests Treg activation as a central mechanism in anti-CD4-mediated tolerance induction. This review summarizes the current knowledge on the role of Treg in peripheral tolerance, addresses the putative mechanisms of Treg mediated suppression and discusses the clinical potential of harnessing Treg suppressive activity through CD4 stimulation.